Dimension of Librarians’ Mobile Information Behavior in an Openness Paradigm Era - Arif, Zuraidah; Abdul Rahman, Abd Latif; Mohammed Ghazali, Asmadi; Mohd Ghazali, Muhammad Faizal Iylia (2015)
Mobile information is a significant access point for human information activities. Theories and models of human information behavior have developed over several decades but have not yet considered the role of the user’s computing device in digital information interactions. This paper reviews the literature that leads to developing a conceptual framework of a study on the librarian mobile information behavior. Based on the literature review, dimensions of mobile information behavior are identified, namely, dimension information needs, dimension information access, information retrieval and dimension of information use. The study is significant to understand the nature of librarians’ behavior in searching, retrieving and using of information via the mobile device. Secondly the study would provide suggestions about various kinds of mobile applications which library can provide for their staff to improve their services.